Intellectual capital in the healthcare sector: a systematic review and critique of the literature. Issue 1 (June 2015) - Evans, Jenna; Brown, Adalsteinn; Baker, G.
Abstract Background Variations in the performance of healthcare organizations may be partly explained by differing "stocks" of intellectual capital (IC), and differing approaches and capacities for leveraging IC. This study synthesizes what is currently known about the conceptualization, management and measurement of IC in healthcare through a review of the literature. Methods Peer-reviewed papers on IC in healthcare published between 1990 and 2014 were identified through searches of five databases using the following key terms: intellectual capital/assets, knowledge capital/assets/resources, and intangible assets/resources. Articles deemed relevant for inclusion underwent systematic data extraction to identify overarching themes and were assessed for their methodological quality. Results Thirty-seven papers were included in the review. The primary research method used was cross-sectional questionnaires focused on hospital managers' perceptions of IC, followed by semi-structured interviews and analysis of administrative data. Empirical studies suggest that IC is linked to subjective process and performance indicators in healthcare organizations. Although the literature on IC in healthcare is growing, it is not advanced. In this paper, we identify and examine the conceptual, theoretical and methodological limitations of the literature. Conclusions The concept and framework of IC offer a means to study the value of intangible resources in healthcare organizations, how to manage systematically these resourcestogether, and their mutually enhancing interactions on performance. We offer several recommendations for future research.